Pengaruh Pemberian Ekstrak Daun Sukun (Artocarpus altilis F.) terhadap Penurunan Kadar Malondialdehid (MDA) pada Tikus (Rattus norvegicus) Model Diabetes Melitus - Winarti, Gresmita Rindi; Nurwati, Ida; Hikmayani, Nur Hafidha (Nexus Biomedika, 2014)
Background: Diabetes mellitus is a chronic metabolic disease that causes increased free radical activity in the body. Excessive free radicals contribute to diabetes complications. The free radicals will react with lipids and then they can form malondialdehyde. This free radicals can be neutralized by antioxidants. Breadfruit (Atrocarpus altilis F.) leaf contains flavonoids and phenolics which serve as antioxidants. This research aimed to determine the effect of breadfruit leaf extract on malondialdehyde levels in diabetic rats. Methods: This was an experimental research using posttest only control group design. Subjects were 30 male white rats, three months old with average body weight of 160-200 g. Subjects were randomly divided into five treatment groups: Normal group, negative control group, treatment group I, treatment group II, and treatment group III. All subjects of the groups, except normal group, were induced by 65 mg/kgBW streptozotocin (STZ) and 230 mg/kgBW nicotinamide (NA). Each subjects in normal and negative control group were administered 2 ml/kgBW/day Natrium Carboxymethyl Cellulose (Na-CMC), whereas treatment groups I, II, and III were administered breadfruit leaf extract at doses of 200 mg/kgBW/day, 400 mg/kgBW/day, and 800 mg/kgBW/day, respectively. The treatments were done for 14 days. Malondialdehyde levels were measured from blood samples collected via retro-orbital veins. Data were analyzed using Kruskal-Wallis test followed by Mann-Whitney U tests (a=0.05). Results: Kruskal-Wallis test showed a significant difference of MDA levels among five groups (p<0.001). Statistically significant differences of MDA levels were further found in all pairs of two-group comparisons, except between the negative control group and the treatment group I (p=0.690). Conclusion: Breadfruit leaf extract could decrease malondialdehyde levels in diabetic rats induced by STZ-NA. The dose of 800 mg/kgBW/day of breadfruit leaf extract showed the greatest effect. Keywords: Breadfruit leaf extract, MDA, Diabetes mellitusÂ